Activities of International Financial Institutions in reaction to war in Ukraine - Panteleymonov, Dmytro; Hnát, Pavel, 1981-; Smělá, Monika; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
Financial aid provided by International financial institutions has grown greatly in Ukraine to help alleviate some of the negative effects of the ongoing conflict between Russia and Ukraine and a significant economic turmoil in the latter, as a result. Through a mixed-methods approach, this study aims to provide an in-depth analysis of the IFIs activities in Ukraine during the war, particularly in the energy sector, and evaluate their effectiveness in relieving the consequences of the conflict. To conduct a research the data from official reports, press releases, and other relevant publications of a number of IFIs have been gathered and a thorough SWOT analysis of particular EBRD energy programs in Ukraine has been carried out. The thesis thus has contributed to the existing literature on the role of IFIs in supporting countries during times of conflict and instability.
Vedoucí práce: Pavel Hnát
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses